JISMОNIY TARBIYА YO‘NALISHI TALАBАLАRIDА PEDAGОGIK TOLERАNTLIKNI RIVOJLАNTIRISHNING AMALIYOTDАGI HOLАTI (UBS Scientific Bulletin, 2025)
In the article, the development of pedagogical tolerance amongstudents of physical education was considered and analyzed in practice.